The role of ecosystem engineers in the ecomorphological development of intertidal habitats - Walles, Brenda (Wageningen University, 2015)
The role of ecosystem engineers in the ecomorphological development of intertidal habitats: General introduction & outline of the thesis; The ecosystem engineer Crassostrea gigas affects tidal flat morphology beyond the boundary of their reef structures,...